The colonial official as ethnographer; VOC documents as resources for social history in eastern Indonesia - Hägerdal, Hans (Wacana, Journal of the Humanities of Indonesia, 2012)
The present article departs from the inherent problems of grasping the voice of the subaltern other in a colonial context. While postcolonial theoreticians have occasionally spoken pessimistically about the possibilities of reconstructing the agency of dominated categories of non-Westerners, recent research on early Southeast Asia has on the contrary envisaged new lines of inquiry through an ingenious use of the extant sources, preferably through interdisciplinary communication. But can we use the colonial archive in order to highlight social history in non-literate societies such as those of eastern Indonesia where the colonial texts do not resonate with the indigenous ones? This article scrutinizes materials from the VOC (Vereenigde Oost-Indische Compagnie) post in Kupang (1653-1800) in order to find data usable for such a history. It is argued that letters, reports, legal minutes, diaries, etcetera. have a good potential due to the regularity and minute detail of the record.